Collaborative Movement: What Queering Dance Makes Possible - Carter, Claire (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
Collaborative Movement focuses on an ongoing research collaboration centred on supporting trans/genderqueer/non-binary/queer community dance/movement programming and mentorship in Regina, Treaty 4 territory. Incorporating queer feminist community research methods, this article demonstrates that collaborations between community organizations and academia can be productive in their grounding of ideas (about gender and bodies) in everyday complexities and specificities of place in ways that hold potential for new forms of interaction, new ways of relating to each other, and new possibilities for action.